Social and Intellectual Networking in the Early Middle Ages - Kelly, Michael; Fazioli, K. Patrick (punctum books, 2023)
Social and Intellectual Networking in the Early Middle Ages seeks to expand our understanding of early medieval connectivity by interrogating social and intellectual collaborations, competitions, and communications among persons, places, things, and ideas in the European and Mediterranean West during the second half of the first millennium CE. In so doing, its contributors explore the existence, performance, and sustainability of diverse political, scholarly, ecclesiastical, and material networks via manuscripts, artifacts, and theories framed by two broad interpretive categories. The first examines networks of scholars, writers, and the social and political histories related to their productions. The second imagines the transmission of "knowledge" as information, rhetoric, object, and epistemic grounding. In addition, the book rigorously investigates the theoretical possibilities and problems of researching early medieval networks, attempts to re-construct historical networks, and critically analyzes the concept of "information.